High intraspecific variability in the diet of a deep-sea nematode: Stable isotope and fatty acid analyses of Deontostoma tridentum on Chatham Rise, Southwest Pacific. (March 2015) - Leduc, Daniel; Brown, Julie C.S.; Bury, Sarah J.; Lörz, Anne-Nina
Abstract: Small deep-sea organisms may exhibit a high degree of intraspecific variability in diet due to their ability to exploit a wide range of food sources and patchiness in food availability. Trophic interactions of small deep-sea benthic organisms, however, remain poorly understood. Here we describe spatial variation in diet/trophic level of the common deep-sea nematode Deontostoma tridentum on Chatham Rise, Southwest Pacific, using carbon and nitrogen stable isotope and fatty acid analyses. We also analysed sediment organic matter (SOM) and compared the isotopic composition of D. tridentum to other benthic and suprabenthic macrofaunal taxa with a variety of feeding modes. Variability in D. tridentum δ 13 C and δ 15 N signatures was high both among sites and within a single site on the southern flank of Chatham Rise. Among-site variation in SOM δ 13 C signatures was not sufficient to explain variation in nematode isotopic signatures. The presence of a positive correlation between δ 13 C and δ 15 N signatures of D. tridentum (both among and within sites) could suggest that differences in trophic level is the cause behind this variation. Nitrogen isotope data suggest the presence of 1–3 trophic levels in this species, which may reflect differences in prey availability, nematode body size, or habitat (benthic versus epizoic). Nematode δ 15 N values exceeded those of all other taxa we investigated, including other predators, but reasons for this enrichment remain unclear. The fatty acid composition of D. tridentum did not vary substantially between sites and was characterised by relatively high levels of 18:1n9 (15–20%) and polyunsaturated fatty acids (PUFAs; ~22%). Although limited inferences can be made based on fatty acid composition due to the potential impacts of non-dietary factors, high levels of PUFAs indicate that D. tridentum represents a good source of these essential nutrients to higher trophic levels. In conclusion, our results show that (1) some deep-sea organisms exhibit a high degree of intraspecific variability in diet, and (2) nematodes may be an important source of PUFAs for larger animals in deep-sea environments, where the quality of SOM is low. Highlights: Little is known about the variation in diet of deep-sea fauna. We measured δ 13 C and δ 15 N values and fatty acid makeup of predatory nematode. There was high variability in nematode isotopic signatures. This variability may be linked to differences in trophic level (1–3). High level of polyunsaturated fatty acids means nematodes are nutritious preys.